Beckman Model 803 voltage regulators on circuit diagram - Armstrong & Hess (1950)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products, in this case voltage regulators.
Keywords: Charts, diagrams, etc.; Voltage regulators; Beckman Instruments, Inc.